2019
DOI: 10.1093/ajcn/nqy228
|View full text |Cite
|
Sign up to set email alerts
|

A multicountry randomized controlled trial of comprehensive maternal nutrition supplementation initiated before conception: the Women First trial

Abstract: BackgroundReported benefits of maternal nutrition supplements commenced during pregnancy in low-resource populations have typically been quite limited.ObjectivesThis study tested the effects on newborn size, especially length, of commencing nutrition supplements for women in low-resource populations ≥3 mo before conception (Arm 1), compared with the same supplement commenced late in the first trimester of pregnancy (Arm 2) or not at all (control Arm 3).MethodsWomen First was a 3-arm individualized randomized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
140
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(168 citation statements)
references
References 35 publications
1
140
1
1
Order By: Relevance
“…Of these, a total of 72 unique studies, with 314 associated papers, were identified for inclusion based on our pre-defined inclusion and exclusion criteria ( Figure 1). Eight studies were included in the review, but did not contribute data to the meta-analyses for reasons including incomplete data and no reported outcomes of interest [48][49][50][51][52][53][54][55]. Subgroup analyses were conducted for the following comparisons: zinc vs. placebo, iron vs. placebo, and MMN vs. IFA supplementation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, a total of 72 unique studies, with 314 associated papers, were identified for inclusion based on our pre-defined inclusion and exclusion criteria ( Figure 1). Eight studies were included in the review, but did not contribute data to the meta-analyses for reasons including incomplete data and no reported outcomes of interest [48][49][50][51][52][53][54][55]. Subgroup analyses were conducted for the following comparisons: zinc vs. placebo, iron vs. placebo, and MMN vs. IFA supplementation.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies were conducted in Latin America and the Caribbean [48,[113][114][115][116][117][118], and only one trial was conducted in Europe and Central Asia (Turkey; [52]). Two trials were multi-country studies [55,119], conducted in countries representative of multiple geographical regions. A summary of study characteristics can be found in the Supplementary Materials, Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…Other available evidence, from three trials that started preconception maternal supplementation at least 3 months prior to conception, is mixed. A recent multicountry (Democratic Republic of the Congo, Guatemala, India, and Pakistan) randomized controlled trial showed no difference in birth outcomes in the group that received daily LNS starting at least 3 months before conception compared with the group that received LNS starting late in the first trimester of pregnancy, though birth outcomes in both LNS groups were improved relative to the control group that did not receive supplementation (Hambidge et al, 2019). An earlier food-based intervention in India showed no difference in birth weight among the infants of women who were provided with a nutrient-dense daily snack prior to conception and through pregnancy, compared with the infants of women provided a similar snack but with low micronutrient content (control; Potdar et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is limited evidence on the impact of maternal nutrition interventions during the preconception period, including the importance of the specific timing and duration of the preconception intervention, on birth outcomes and child growth. A few studies have evaluated the effect of preconception nutrition interventions on birth outcomes (Hambidge et al, 2019;Nguyen et al, 2017;Potdar et al, 2014;Ramakrishnan et al, 2016). In the most recent trial, conducted in four low-and middle-income countries, maternal supplementation with a lipid-based nutrient supplement (LNS) starting at least 3 months before conception improved foetal growth, but the impact on foetal growth did not significantly differ from the impact observed when the supplement was started late in the first trimester (Hambidge et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Here we report the newborn anthropometric data for the combined S. Asian sites participating in the Women First Preconception Maternal Nutrition Trial [30].…”
Section: Introductionmentioning
confidence: 99%